Klasifikasi Suara Pria Menggunakan Metode Fast Fourier Transform (FFT) - Pattraksha, Anak Agung Gde Ramananda Kartikeya; Muliantara, Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 2 (2023): JNATIA Vol. 1, No. 2, Februari 2023DO - 10.24843/JNATIA.2023.v01.i02.p01, 2023)
Every Person has a different voice. By gender, the voice type is divided into six parts, namely soprano, soprano and tenor for girls and tenor, baritone and bass for men. Each type of sound has a by different range and with different frequencies: this study classified the voice type in Men using Fast Fourier Transform (FFT) method by recording each user's voice , then will be processed by FFT method to obtain the appropriate sound range. sound This study has obtained results with up to 80% accuracy. The results obtained from this study are quite consistent and there is evidence that the FFT method can be used in digital signal processing. Keywords:  Fast Fourier Transform, Sound type, Men, Frequency